Aktivitas Antioksidan Ekstrak Metanol Daun Pepaya (Carica papaya L) dengan Metode 2, 2 – Diphenyl - 1 – Picrylhydrazil (DPPH) - Harni Sepriyani (Jurnal Penelitian Farmasi Indonesia, 2020)
Antioxidants are compounds that can inhibit or prevent the oxidation process of other compounds caused by free radicals. Free radicals can cause nucleic acid mutations. Based on the source, antioxidants are grouped into synthetic antioxidants and natural antioxidants. Papaya leaf is one of the plants used in traditional medicine which is considered a natural antioxidant. The purpose of this study was to study the antioxidant activity of papaya extract methanol through IC50 values. The method used in this research is 2,2-diphenyl-1-picrylhydarzil (DPPH) method. The results of this study are referred to as IC50 values ​​of 884.8272 ppm. This means that methanol extract papaya leaves has very weak antioxidant activity.